Mice deficient in UXT exhibit retinitis pigmentosa-like features via aberrant autophagy activation. Issue 8 (3rd August 2021) - Pan, Mingyu; Yin, Yue; Wang, Xinxia; Wang, Quanyi; Zhang, Lele; Hu, Haiyang; Wang, Chen
ABSTRACT: UXT (ubiquitously expressed prefoldin like chaperone), a small chaperone-like protein, is widely expressed in diverse human and mouse tissues and is more abundant in retina and kidney. However, the functional characterization of UXT at tissue level was largely unknown. Here, we reported that mice deficient in UXT exhibited salient features of retinal degenerative disease, similar to retinitis pigmentosa. Conditional knockout (CKO) of Uxt led to retinal degeneration and pigmentation in mice retina along with significant alterations of retinitis pigmentosa-related genes, which indicated UXT might be associated with retinal degenerative disease sharing key features to retinitis pigmentosa. Consistently, the electroretinogram (ERG) responses were dramatically impaired in uxt CKO retinas. Strong degenerative features were observed in uxt CKO retinas, including specific and progressive reduction of photoreceptor cells and increased numbers of apoptotic cells. Intriguingly, macroautophagic/autophagic ﬂux was enhanced in uxt CKO retina. Mechanistically, we found UXT was indispensable to suppress photoreceptor apoptotic cell death by inhibiting autophagy through regulating the activity of MTOR (mechanistic target of rapamycin kinase), a key negative regulator of autophagy. Conversely, knockdown of UXT induced the robust expression of the canonical autophagy-related genes and boosted autophagic ﬂux and apoptosis, finally resulting in severe retina degeneration in uxt CKO mice. Taken together, our study reveals a vital role of UXT in preventing retina from degeneration. The loss of UXT results in a hyper-autophagic state leading to massive retinal degeneration. Therefore, UXT may be a crucial target for retinal degenerative disease. Abbreviations : 3-ma: 3-methyladenine; casp3: caspase 3; cko: conditional knockout; erg: electroretinogram; gapdh: glyceraldehyde-3-phosphate dehydrogenase; map1lc3b/lc3b: microtubule-associated protein 1 light chain 3; mtor: mechanistic target of rapamycin kinase; parp: poly (adp-ribose) polymerase family; rna-seq: rna sequencing; rp: retinitis pigmentosa; rps6kb1/s6k: ribosomal protein s6 kinase b1; sqstm1: sequestosome 1; tunel: terminal deoxynucleotidyl transferase mediated dutp nick-end labeling; uxt: ubiquitously expressed prefoldin like chaperone.